EKSTRAK MENGKUDU (Morinda citrifolia L) SEBAGAI ANTIMICROBA TERHADAP Streptococcus viridans SECARA IN VITRO (THE NONI EXTRACT (Morinda citrifolia L) AS ANTIMICROBA TOWARD Streptococcus viridans IN VITRO) - Mahtuti, Erni Yohani; Ibaadillah, Afrihal Afiif (Journal Nursing Care and Biomolecular, 2017)
Streptococcus viridans infection is serious when bacteria enter other areas of the body, to the bloodstream causing endocarditis, heart damage, kidney failure. Symptoms: fatigue, fever, weight loss, and shock, organ failure insufficient blood; Intra-abdominal infections; meningitis, swelling of the meninges to death. Bacteria cause 50% of cases endocarditis. Treatment with high-dose antibiotics is dangerous, causing resistance. Noni (Morinda citrifolia) as antiviral, antibacterial, antiinflammatory has 150 content phytonutrients, increases endurance and improves cell. The objectives were to know the MIC and MBC of noni extract and penicillin to Streptococcus viridans in vitro. The research is true experiment, RAL design, bacteria sample and noni extract. Free variable, concentration of noni extraction, penisillin 5Î¼L, 7.5 Î¼L and 10 Î¼L. Variable depends the amount of bacteria. Research location in Laboratory Microbiology and Bio Medical University Muhammadiyah of Malang. Method agar plate dilution. Collecting data the number of colonies Streptococcus viridans, One-Way Anova analysis. The results of MIC 5Î¼L and MBC 10 Î¼L. Analysis p = 0.00 <0.01, Ho rejected, Hi accepted is effectiveness of noni extract and penicillin against Streptococcus viridans as antimicrobial compound in vitro. Effectiveness ofÂ  regression linear noni 63.8% and pensillin 63.9% in inhibiting the growth Â Streptococcus viridans in vitro.